A modified 17-4PH high-toughness stainless steel material and preparation method thereof
By mixing 17-4PH stainless steel powder with 304 stainless steel powder and adding titanium powder, aluminum powder and graphene to form a titanium carbide network structure and dense oxide layer, the problem of insufficient toughness of the 17-4PH stainless steel material is solved, significantly improving the toughness and corrosion resistance of the material, and improving the product quality and operating efficiency after injection molding.
Patent Information
- Application Number
- CN202410436050.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-04-11
AI Technical Summary
The toughness of 17-4PH stainless steel material is poor, which leads to prone to product breakage during blank repair after injection molding, which increases the defect rate and affects the working efficiency.
A mixture of 17-4PH stainless steel powder and 304 stainless steel powder is used as the substrate, and titanium powder, aluminum powder and graphene are added. Through heat treatment and pretreatment technology, a titanium carbide network structure and dense oxide layer are formed to improve the toughness and corrosion resistance of the material.
The toughness and plasticity of 17-4PH stainless steel material is significantly improved, the brittleness is reduced, the impact resistance and oxidation resistance of the material are enhanced, and the product quality and operating efficiency after injection molding are improved.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal materials, and more specifically, to a modified 17-4PH high-toughness stainless steel material and a preparation method thereof. Background Art
[0002] 17-4PH stainless steel is a typical martensitic precipitation hardening stainless steel with excellent corrosion resistance, high temperature resistance, wear resistance, creep resistance, good appearance gloss, and high forming strength. It can also meet the processing requirements of large-size 3D printed parts and has a wide range of uses in many fields such as medical equipment, automobiles, military industry, aviation, and nuclear industry.
[0003] Metal injection molding (MIM) is a molding method that injects a mixture of metal powder and binder into a model. First, the selected metal powder is mixed with the binder, then the mixture is granulated and then injected into the required shape. The binder imparts its viscous flow characteristics to the mixture, which helps to form, fill the mold cavity and uniformity of powder filling. After forming, the binder is removed, and the degreased blank is sintered. The sintered product is further densified, heat treated or machined. The sintered product not only has the same complex shape and high precision as the products obtained by plastic injection molding, but also has physical, chemical and mechanical properties close to those of forgings. MIM technology combines the advantages of powder metallurgy and plastic injection molding, breaking through the limitations of traditional metal powder compression molding process on product shape. At the same time, it utilizes the characteristics of plastic injection molding technology that can form parts with complex shapes in large quantities and with high efficiency. It has become a molding technology for modern manufacturing of high-quality precision parts, with advantages that conventional powder metallurgy, machining and precision casting cannot match.
[0004] However, due to the organizational characteristics of 17-4PH, its toughness is poor, its rigidity is strong, and it is not easy to correct deformation by plastic molding. Therefore, after injection molding, when the blank is repaired, the product will break due to the brittleness and low toughness of the blank, which increases the defective rate and affects the operation efficiency. Summary of the invention
[0005] In order to improve the toughness of 17-4PH material, improve the shaping effect of products, and improve operating efficiency, the present application provides a modified 17-4PH high-toughness stainless steel material and a preparation method thereof.
[0006] In the first aspect, the present application provides a modified 17-4PH high-toughness stainless steel material, which adopts the following technical solution:
[0007] A modified 17-4PH high-toughness stainless steel material comprises the following raw materials in parts by weight: 100 parts of stainless steel powder, 6-8 parts of a binder, 0.1-0.4 parts of titanium powder, 0.2-1 parts of aluminum powder and 0.15-0.2 parts of graphene, wherein the stainless steel powder comprises 17-4PH stainless steel powder and 304 stainless steel powder in a mass ratio of 7-9:1-3.
[0008] By adopting the above technical scheme, a mixture of 17-4PH stainless steel powder and 304 stainless steel powder is used as the substrate. The 17-4PH stainless steel powder has good strength and hardness, and the 304 stainless steel powder belongs to austenitic stainless steel material, which has high toughness and plasticity. Therefore, the toughness and plasticity of 17-4PH stainless steel products can be improved and the brittleness can be reduced. In addition, the introduction of graphene can hinder the migration of grain boundaries and refine the grains. Moreover, when the stainless steel material breaks, the breaking of graphene, the conversion of crack flakes and the extraction of graphene can make the graphene consume the crack expansion energy in various forms inside the material, thereby increasing the crack expansion path in the stainless steel material, improving the crack expansion resistance, improving the fracture toughness, improving the density of the stainless steel material, and improving the High hardness and impact resistance, titanium powder can fully strengthen the matrix, aluminum powder can react with nickel in 17-4PH stainless steel powder, after strong bond and complex atomic arrangement, disordered to ordered metal compounds precipitated in stainless steel material, so as to obtain high plasticity and toughness, and aluminum powder can be oxidized during heat treatment to form a dense aluminum oxide layer, which can improve the oxidation resistance of stainless steel material; titanium powder and aluminum powder can effectively improve the toughness of stainless steel material; and titanium powder and graphene can form titanium carbide after sintering, which is a quasi-continuous network distribution, can bear loads and strengthen grain boundaries, achieve a large degree of plastic deformation, and ensure good interface strength. The network structure has good bearing capacity, can bear the main load, and improve strength and elastic modulus.
[0009] Optionally, the graphene is subjected to the following modification pretreatment:
[0010] Adding graphene to anhydrous ethanol, adding a dispersant, and performing ultrasonic dispersion to obtain a graphene suspension;
[0011] Add nano titanium nitride and yttrium oxide to the suspension, ultrasonically disperse for 20-30 minutes, ball mill for 20-24 hours, and vacuum dry. The ratio of graphene, nano titanium nitride and yttrium oxide is 1:10-15:0.15-0.2.
[0012] By adopting the above technical scheme, polyvinyl pyrrolidone is used as a dispersant, which can improve the dispersion effect of graphene through the synergistic effect of electrostatic dispersion mechanism and steric hindrance dispersion mechanism, nano titanium nitride can promote grain growth, hinder crack propagation, and enhance material toughness, and yttrium oxide can play a pinning role, inhibiting grain boundary diffusion and surface diffusion of grains, thereby inhibiting grain growth. Therefore, the use of nano titanium nitride and yttrium oxide can improve the effect of graphene on promoting grain growth of stainless steel materials, which is beneficial to improving the comprehensive performance of stainless steel materials, and yttrium oxide can also play a role in strengthening the bonding phase, thereby improving the corrosion resistance of stainless steel materials.
[0013] Optionally, the added amount of titanium powder is 9% to 30% of the total mass of titanium powder and aluminum powder.
[0014] By adopting the above technical solution, the dosage of titanium powder and aluminum powder is within the above range, which can effectively reduce the brittleness of the stainless steel material and increase the toughness and plasticity.
[0015] Optionally, the binder comprises polyethylene glycol, polyvinylidene fluoride, sodium silicate and stearic acid in a mass ratio of 7-8:2-3:1-1.5:0.5-1.
[0016] By adopting the above technical scheme, liquid sodium silicate has lubricating and anti-corrosion effects. When mixed with stainless steel powder, it can be intimately wetted with the stainless steel powder components, so that the stainless steel powder has better fluidity and lubricity, and is more suitable for injection molding. The green body formed has a complete morphology, fewer internal holes, and a regular internal structure. It can still maintain its original shape and has no external defects after degreasing. However, sodium silicate has a hydrophilic structure, and excessive hygroscopicity will affect the long-term anti-corrosion behavior of stainless steel materials. Therefore, polyvinylidene fluoride with a hydrophobic structure is used in combination with sodium silicate. Polyvinylidene fluoride will not absorb moisture in a humid environment, so the two complement each other in terms of moisture resistance and corrosion resistance, while improving the corrosion resistance of stainless steel materials, reducing the moisture absorption rate.
[0017] Optionally, the binder further includes an auxiliary wetting agent, the mass ratio of the auxiliary wetting agent to polyethylene glycol is 0.2-0.8:1, and the preparation method of the auxiliary wetting agent is as follows:
[0018] The silicon powder and flake graphite are mixed and ground for 15-20 minutes, and then the mixture is added with a uniformly mixed NaCl-NaF mixed salt and the grinding is continued for 15-20 minutes. Then, the mixture is heated to 1300-1350°C in an argon atmosphere, kept warm for 2.5-3 hours, cooled to room temperature, washed with distilled water, and dried at 100-110°C for 12-14 hours. The mass ratio of silicon powder to flake graphite is 1:2-3.
[0019] By adopting the above technical scheme, molten salt is used as a medium, based on the dissolution of silicon in the molten salt, the mass transfer rate is significantly improved, and at the same time, it is evenly diffused to the graphite surface and nano-silicon carbide is generated in situ, and the silicon carbide coats the graphite powder. Since there are a large number of silicon carbide crystal nuclei on the surface of the silicon carbide-coated graphite, the wettability between the stainless steel powder and the binder is improved, and the bonding force between the stainless steel powder and the binder is improved. After heat treatment, a strong bond is formed, which has a strengthening and toughening effect on the stainless steel material. When the stainless steel material is subjected to external force, due to the debonding of the internal nano-silicon carbide, crack deflection, bridging and pull-out can effectively increase the crack propagation path, so the mechanical properties of the stainless steel material can be increased.
[0020] Optionally, the silicon powder particle size is 1-9 μm, and the flake graphite particle size is 45-75 μm.
[0021] By adopting the above technical solution, silicon powder with smaller particle size can diffuse quickly to flake graphite with larger particle size in the molten salt medium, grow in situ on its surface, and form silicon carbide whiskers.
[0022] Optionally, the particle size of the 17-4PH stainless steel powder is 15-53 μm.
[0023] Optionally, the tap density of the 304 stainless steel powder is 3.9-4.2 g / cm 3 , fluidity ≤30s / 50g, compressibility ≥6.55g / cm 3 .
[0024] In a second aspect, the present application provides a method for preparing a modified 17-4PH high-toughness stainless steel material, using the following technical solution:
[0025] A method for preparing a modified 17-4PH high-toughness stainless steel material comprises the following steps:
[0026] The titanium powder and graphene are added to anhydrous ethanol, ultrasonically mixed and then ball-milled, and then the temperature is raised to 550-600° C., and the temperature is kept at a pressure of 40-50 MPa for 4-6 minutes to prepare a premix;
[0027] The premix is mixed evenly with stainless steel powder and aluminum powder, and kneaded at 100-160° C. for 20-30 minutes to obtain a mixed powder;
[0028] The mixed powder is mixed with a binder, stirred at 160-165°C, and then granulated, injection molded, degreased, and heat treated.
[0029] By adopting the above technical scheme, graphene has strong interlayer van der Waals force, and has poor chemical compatibility and wettability with titanium powder, aluminum powder, etc., which makes graphene easy to agglomerate and unevenly dispersed, so it is difficult to ensure the density of stainless steel material. Therefore, the graphene is first mixed with titanium powder. After low-temperature sintering, the grains can be refined. The refined grains play a role of fine grain strengthening on the one hand, and can improve plasticity on the other hand. The boundaries of powder particles usually evolve into grain boundaries, so the graphene on the surface of the powder particles is often located at the grain boundaries after sintering. The graphene at the grain boundaries hinders the migration of grain boundaries, so that the graphene strengthens the titanium powder. Therefore, while improving the uniformity of graphene, it can also further increase the plasticity of titanium powder, thereby improving the bearing capacity of stainless steel materials and improving toughness.
[0030] Optionally, the specific method of the heat treatment is: solution treatment at 925-1040°C for 1-2h, and deep cryogenic treatment at (-10~0)°C for 1-2h.
[0031] By adopting the above technical solution, the porosity of the product after degreasing after heat treatment is reduced, the grains can be further refined, which is beneficial to hinder the movement of dislocations, improve the strength and enhance the corrosion resistance.
[0032] In summary, this application has the following beneficial effects:
[0033] 1. Since the present application uses 304 stainless steel powder to improve the toughness of 17-4PH stainless steel powder, and adds a certain amount of titanium powder, aluminum powder and graphene, the titanium powder and graphene can form titanium carbide, presenting a continuous network distribution in the stainless steel material, improving the bearing capacity of the stainless steel material, and the titanium powder can fully strengthen the matrix, and the aluminum powder can form layered ordered metal compounds, and when mixed at high temperature, a dense aluminum oxide protective layer is generated, which improves the plasticity and fracture toughness of the stainless steel material.
[0034] 2. In the present application, nano titanium nitride and yttrium oxide are preferably used to pretreat graphene. Both titanium nitride and yttrium oxide can refine the grains, making the structure of the stainless steel material more uniform and dense, thereby improving the hardness and fracture toughness of the material. Yttrium oxide can also further improve the corrosion resistance of the material.
[0035] 3. In this application, polyethylene glycol, polyvinylidene fluoride, sodium silicate and stearic acid are preferably used to prepare the binder, which can improve the fluidity and filling property of the stainless steel powder. The combination of sodium silicate and polyvinylidene fluoride can also improve the corrosion resistance of the stainless steel material. In addition, a certain auxiliary wetting agent is added to the binder to improve the wetting ability of the binder on the stainless steel powder, improve the interfacial bonding effect and improve the density. DETAILED DESCRIPTION
[0036] The following examples further illustrate the present application in detail. Example
[0037] Example 1: A modified 17-4PH high-toughness stainless steel material, the raw material dosage is shown in Table 1, wherein the stainless steel powder includes 80kg 17-4PH stainless steel powder mixed with 20kg 304 stainless steel powder, the particle size of the 17-4PH stainless steel powder is 53μm, and includes the following components in mass percentage: Cr17.5wt%, Ni5wt%, Cu5wt%, Nb0.45wt%, C0.07wt%, Si1.0wt%, Mn1.0wt%, P0.04wt%, S0.03wt%, and the balance is Fe, and the tap density of the 304 stainless steel powder is 4.2g / cm 3 , fluidity ≤30s / 50g, compressibility ≥6.55g / cm 3 , and includes the following components in mass percentage: Cr20wt%, Ni12wt%, Mn0.2wt%, Si0.8wt%, C<0.03wtt%, P<0.03wt%, S<0.02wt%, O<0.3wt%, and the balance is Fe. The binder includes polyethylene glycol 20000, polyvinyl butyral and stearic acid in a mass ratio of 7:2:1. The polyethylene glycol 20000 is selected from Jiangsu Maoheng Chemical Co., Ltd. and the item number is P045. The binder is prepared by adding 7kg of polyethylene glycol to water to form a solution with a concentration of 70%, adding 2kg of polyvinyl butyral and 1kg of stearic acid, and mixing them evenly. The amount of titanium powder added is 0.99% of the total weight of titanium powder and aluminum powder;
[0038] The preparation method of the modified 17-4PH high-toughness stainless steel material comprises the following steps:
[0039] S1. Add titanium powder and graphene to anhydrous ethanol, mix by ultrasonication and then ball mill, then heat to 600°C, keep warm for 6 minutes at a pressure of 40 MPa to prepare a premix;
[0040] S2, the premix is mixed with stainless steel powder and aluminum powder, and kneaded at 160° C. for 20 min to obtain a mixed powder;
[0041] S3, the mixed powder is mixed with a binder, stirred at 160°C, and then granulated to obtain a tap density of 4.68 g / cm 3 Spare materials;
[0042] S4, injection molding the spare material on an injection molding machine to obtain an injection blank, the injection temperature is 200°C, the injection pressure is 100MPa, and the mold temperature is 120°C;
[0043] S5, catalytically degreasing the injection blank with nitric acid to obtain a degreased blank, the degreasing temperature is 110° C., the acid flow rate is 3.5 ml / min, and the acid flow time is 2 h;
[0044] S6. The degreased blank is heat treated, and the heat treatment process is: solution treatment at 1040°C for 1 hour and deep cooling treatment at 0°C for 1 hour.
[0045] Table 1 Raw material dosage of modified 17-4PH stainless steel material in Examples 1-4
[0046] Raw material / kg Example 1 Example 2 Example 3 Example 4 Stainless steel powder 100 100 100 100 Binder 8 8 8 6 Titanium powder 0.1 0.4 0.4 0.1 Aluminum powder 1 1 0.2 0.2 Graphene 0.2 0.2 0.2 0.15
[0047] Example 2-4: A modified 17-4PH high-toughness stainless steel material, which is different from Example 1 in that the amounts of raw materials are as shown in Table 1.
[0048] Example 5: A modified 17-4PH high-toughness stainless steel material, which is different from Example 1 in that the graphene is subjected to the following modification pretreatment:
[0049] 0.2 kg of graphene was added to 5 kg of anhydrous ethanol, and 0.02 kg of dispersant was added, and ultrasonic dispersion was performed to obtain a graphene suspension, wherein the dispersant was polyvinyl pyrrolidone;
[0050] Nano-titanium nitride and yttrium oxide were added to the suspension, ultrasonically dispersed at a power of 200 W for 30 minutes, ball milled for 24 hours, with a ball-to-material ratio of 5:1 and a ball milling speed of 300 r / min. The suspension was vacuum dried at 100°C for 2 hours. The ratio of graphene, nano-titanium nitride and yttrium oxide was 1:15:0.2. The particle size of nano-titanium nitride was 20 nm, and the particle size of yttrium oxide was 1.5 μm.
[0051] Example 6: A modified 17-4PH high-toughness stainless steel material, which is different from Example 1 in that the graphene is subjected to the following modification pretreatment:
[0052] 0.2 kg of graphene was added to 5 kg of anhydrous ethanol, and 0.02 kg of dispersant was added, and ultrasonic dispersion was performed to obtain a graphene suspension, wherein the dispersant was polyvinyl pyrrolidone;
[0053] Nano-titanium nitride and yttrium oxide were added to the suspension, ultrasonically dispersed at a power of 200 W for 20 minutes, ball milled for 20 hours, with a ball-to-material ratio of 5:1 and a ball milling speed of 300 r / min. The suspension was vacuum dried at 100°C for 2 hours. The ratio of graphene, nano-titanium nitride and yttrium oxide was 1:10:0.15, the particle size of nano-titanium nitride was 20 nm, and the particle size of yttrium oxide was 1.5 μm.
[0054] Example 7: A modified 17-4PH high-toughness stainless steel material, which differs from Example 5 in that nano-titanium nitride is not added during the modification pretreatment of graphene.
[0055] Example 8: A modified 17-4PH high-toughness stainless steel material, which differs from Example 5 in that yttrium oxide is not added during the modification pretreatment of graphene.
[0056] Example 9: A modified 17-4PH high-toughness stainless steel material, which differs from Example 5 in that the binder includes polyethylene glycol, polyvinylidene fluoride, sodium silicate and stearic acid in a mass ratio of 7:2:1.5:1, polyethylene glycol 20000 is selected from Jiangsu Maoheng Chemical Co., Ltd., with the item number P045. The binder is prepared by adding 7kg of polyethylene glycol to water to form a solution with a concentration of 70%, adding 2kg of polyvinyl butyral, 1.5kg of liquid sodium silicate and 1kg of stearic acid, and mixing well.
[0057] Example 10: A modified 17-4PH high-toughness stainless steel material, which differs from Example 5 in that the binder includes polyethylene glycol, polyvinylidene fluoride, sodium silicate and stearic acid in a mass ratio of 8:3:1:0.5, polyethylene glycol 20000 is selected from Jiangsu Maoheng Chemical Co., Ltd., with the item number P045. The binder is prepared by adding 8 kg of polyethylene glycol to water to form a solution with a concentration of 70%, adding 3 kg of polyvinylidene fluoride, 1 kg of liquid sodium silicate and 0.5 kg of stearic acid, and mixing well.
[0058] Example 11: A modified 17-4PH high-toughness stainless steel material, which is different from Example 9 in that the binder is prepared by adding 7 kg of polyethylene glycol to water to form a solution with a concentration of 70%, adding 2 kg of polyvinyl butyral, 1.5 kg of liquid sodium silicate and 1 kg of stearic acid, mixing evenly, then adding an auxiliary wetting agent, mixing evenly, the mass ratio of the auxiliary wetting agent to the polyethylene glycol is 0.8:1, and the preparation method of the auxiliary wetting agent is as follows:
[0059] The silicon powder and flake graphite were mixed and ground for 15 minutes, and then the mixture was added with a uniformly mixed NaCl-NaF mixed salt and continued to be ground for 15 minutes. Then, the mixture was heated to 1300°C in an argon atmosphere, kept warm for 3 hours, cooled to room temperature, and washed repeatedly with distilled water until the salt disappeared. The mixture was dried at 110°C for 12 hours. The mass ratio of silicon powder to flake graphite was 1:3, the particle size of silicon powder was 9 μm, and the particle size of flake graphite was 45 μm.
[0060] Example 12: A modified 17-4PH high-toughness stainless steel material, which is different from Example 9 in that the binder is prepared by adding 7 kg of polyethylene glycol to water to form a solution with a concentration of 70%, adding 2 kg of polyvinyl butyral, 1.5 kg of liquid sodium silicate and 1 kg of stearic acid, mixing evenly, then adding an auxiliary wetting agent, mixing evenly, the mass ratio of the auxiliary wetting agent to the polyethylene glycol is 0.2:1, and the preparation method of the auxiliary wetting agent is as follows:
[0061] The silicon powder and flake graphite were mixed and ground for 20 minutes, and then the mixture was added with a uniformly mixed NaCl-NaF mixed salt and continued to be ground for 20 minutes. Then, the mixture was heated to 1350°C in an argon atmosphere, kept warm for 2.5 hours, cooled to room temperature, and washed repeatedly with distilled water until the salt disappeared. The mixture was dried at 100°C for 14 hours. The mass ratio of silicon powder to flake graphite was 1:2, the particle size of silicon powder was 9 μm, and the particle size of flake graphite was 45 μm.
[0062] Comparative Example
[0063] Comparative Example 1: A modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that titanium powder, aluminum powder and graphene are not added.
[0064] Comparative Example 2: A modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that no graphene is added.
[0065] Comparative Example 3: A modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that no aluminum powder is added.
[0066] Comparative Example 4: A method for preparing a modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that step S1 is: mixing titanium powder and graphene evenly to prepare a premix.
[0067] Comparative Example 5: A method for preparing a modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that step S6 heat treatment is not performed.
[0068] Comparative Example 6: A method for preparing a modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that no cryogenic treatment is performed during the heat treatment in step S6.
[0069] Comparative Example 7: A method for preparing a modified 17-4PH high-toughness stainless steel material, which differs from Example 1 in that the heat treatment process in step S6 is: solution treatment at 1040°C for 1 hour and failure treatment at 550°C for 1 hour.
[0070] Comparative Example 8: A method for preparing a stainless steel mixed material feedstock, comprising: (1) taking 1 kg of 304 stainless steel powder and 19 kg of 17-4PH stainless steel powder, wherein the particle size difference between the two types of materials is less than 100 μm, mixing them evenly and pouring them into a mixer, preheating them at 180°C for 25 min, and stirring and mixing them evenly; (2) adding 1.6 kg of a binder (POM resin: high-density polyethylene: ethylene-vinyl acetate: wax: stearic acid = 88:7:2:2:1), kneading for 40 min, and then extruding and pelletizing them to prepare a feedstock.
[0071] Performance testing
[0072] The modified 17-4PH high-toughness stainless steel material was manufactured according to the methods in the embodiments and comparative examples, and a 51 mm × 34 mm × 12 mm specimen was made during injection molding. The performance of each group of specimens was then tested according to the following method. Five specimens were taken for each embodiment or comparative example, and the test results were averaged. The test results are recorded in Table 2.
[0073] 1. Tensile strength: refer to GB / T228.1-2010 "Metallic material tensile test part 1: Room temperature test method", and test on WDW-300E tensile testing machine;
[0074] 2. Elongation after fracture: Tested in accordance with GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method";
[0075] 3. Yield strength: Test in accordance with GB / T228.1-2010 "Metallic material tensile test part 1: Room temperature test method";
[0076] 4. Electrochemical corrosion performance: A disc with a size of φ16mm×2mm was cut from the center of the sample, and the test surface was ground and polished to a mirror surface, and installed in a pressed electrochemical cell. The German Zahner Zennium Peo electrochemical workstation was used for electrochemical impedance and dynamic potential polarization tests. The classic three-electrode system was used, with the platinum mesh as the point electrode (CE), the saturated calomel electrode (SCE) as the reference electrode (RE), and the sample as the working electrode (WE). The test scan speed was 1mV / s, and the exposed area of the working electrode was 1cm2. Before the test, the open circuit potential (OCP) time was set to 3000s, the EIS test starting cross-linking positive frequency (AC) was 5mV, and the scanning frequency range was 105~10-2Hz. The anticorrosive medium used was a sodium chloride solution with a mass fraction of 3.5wt%, which was prepared with ultrapure water and molecular pure sodium chloride without deoxygenation treatment. The experiment was carried out at room temperature (25°C), and the data of the impedance spectrum was analyzed and processed by software. Each set of experiments was repeated 3 times under the same environment to ensure the reliability of the test data. The smaller the current density, the stronger the corrosion resistance.
[0077] Table 2
[0078] project Tensile strength / MPa Yield strength / MPa Elongation after fracture / % <![CDATA[Corrosion current density (μA / cm 2 ) <!-- 6 -->]]> Example 1 971 751 12.4 0.587 Example 2 966 748 12.1 0.592 Example 3 953 740 11.3 0.597 Example 4 961 745 11.7 0.589 Example 5 1044 837 15.4 0.434 Example 6 1039 833 15.2 0.438 Example 7 997 795 13.8 0.436 Example 8 1011 804 14.3 0.521 Example 9 1074 959 16.8 0.345 Example 10 1072 955 16.5 0.349 Embodiment 11 1257 1074 18.2 0.215 Example 12 1251 1068 18.0 0.218 Comparative Example 1 786 568 9.7 0.768 Comparative Example 2 812 638 10.5 0.704 Comparative Example 3 802 594 10.1 0.731 Comparative Example 4 838 684 10.7 0.623 Comparative Example 5 787 583 8.9 0.798 Comparative Example 6 821 675 10.8 0.654 Comparative Example 7 813 654 10.7 0.641 Comparative Example 8 765 554 8.5 0.842
[0079] It can be seen from the data in Table 1 that the mass of titanium powder in Example 1 / (mass of titanium powder + mass of aluminum powder) is 9.09%, the mass of titanium powder in Example 2 / (mass of titanium powder + mass of aluminum powder) is 28.57%, and the mass of titanium powder in Example 3 / (mass of titanium powder + mass of aluminum powder) is 66.67%, and the mass of titanium powder in Example 4 / (mass of titanium powder + mass of aluminum powder) is 33.33%. By comparison, the modified 17-4PH stainless steel materials prepared in Examples 1 and 2 have higher tensile strength and yield strength, and are more ductile and crack resistant.
[0080] Compared with Example 1, Examples 5 and 6 also use nano-titanium nitride and yttrium oxide to pretreat graphene. The modified 17-4PH stainless steel materials obtained in this way have better tensile strength, yield strength and elongation after fracture, and can be seen that the toughness is better, the corrosion current density is reduced, and the corrosion resistance is enhanced.
[0081] Compared with Example 5, Examples 7 and 8 did not add nano titanium nitride and yttrium oxide when pretreating graphene. In Example 7, the corrosion current density did not change much, but the toughness decreased significantly, while in Example 8, the corrosion current density increased, and the tensile strength and other properties decreased. This shows that pretreating graphene with nano titanium nitride and yttrium oxide can not only improve the toughness of the modified 17-4PH stainless steel material, but also improve its corrosion resistance.
[0082] Compared with Example 5, Examples 9 and 10 use polyvinylidene fluoride, sodium silicate, polyethylene glycol and stearic acid to prepare the binder. Table 2 shows that the modified 17-4PH stainless steel materials prepared in Examples 9 and 10 have enhanced mechanical properties such as tensile strength and yield strength, improved toughness, reduced corrosion current density, and improved anti-corrosion effect.
[0083] Compared with Example 9, Examples 11 and 12 further added an auxiliary wetting agent to the binder. Table 2 shows that the mechanical properties of the modified 17-4PH stainless steel materials prepared in Examples 11 and 12 are improved, and the corrosion resistance is enhanced.
[0084] In Comparative Example 1, no titanium powder, aluminum powder or graphene was added, in Comparative Example 2, no graphene was added, and in Comparative Example 3, no aluminum powder was added. Table 2 shows that the mechanical properties of the modified 17-4PH stainless steel materials prepared in Comparative Examples 1-3 decreased and their corrosion resistance weakened.
[0085] In Comparative Example 4, titanium powder and graphene were not ball-milled and sintered at low temperature, and the corrosion resistance of the modified 17-4PH stainless steel material was reduced, indicating that pretreatment of titanium powder and graphene can improve the dispersibility of the two and increase the density.
[0086] Comparative Example 5 Compared with Example 1, the degreased blank was not subjected to heat treatment. It can be seen that the tensile strength and other properties of the modified 17-4PH stainless steel material are significantly reduced.
[0087] Compared with Example 1, Comparative Example 6 did not perform cryogenic treatment, while Comparative Example 7 used high-temperature failure instead of low-temperature cryogenic treatment compared with Example 1. Table 2 shows that the tensile strength, yield strength and other properties of the modified 17-4PH stainless steel materials prepared in Examples 6 and 7 are significantly reduced.
[0088] The tensile strength of the stainless steel mixed material feed prepared by the prior art in Comparative Example 8 is not as good as that in Example 1, indicating that its toughness and anti-corrosion effect are not good.
[0089] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A modified 17-4PH high-toughness stainless steel material, characterized in that: The method comprises the following raw materials in parts by weight: 100 parts of stainless steel powder, 6-8 parts of a binder, 0.1-0.4 parts of titanium powder, 0.2-1 parts of aluminum powder and 0.15-0.2 parts of graphene, wherein the stainless steel powder comprises 17-4PH stainless steel powder and 304 stainless steel powder in a mass ratio of 7-9:1-3; The graphene is subjected to the following modification pretreatment: Adding graphene into anhydrous ethanol, adding a dispersant, and ultrasonically dispersing to obtain a graphene suspension; Add nano-titanium nitride and yttrium oxide to the graphene suspension, perform ultrasonic dispersion for 20-30 minutes, ball mill for 20-24 hours, and vacuum dry. The mass ratio of graphene, nano-titanium nitride and yttrium oxide is 1:10-15:0.15-0.
2. The binder comprises polyethylene glycol, polyvinylidene fluoride, sodium silicate and stearic acid in a mass ratio of 7-8:2-3:1-1.5:0.5-1; The binder also includes an auxiliary wetting agent, the mass ratio of the auxiliary wetting agent to polyethylene glycol is 0.2-0.8:1, and the preparation method of the auxiliary wetting agent is as follows: The silicon powder and flake graphite are mixed and ground for 15-20 minutes, and then the mixed NaCl-NaF salt is added and the grinding is continued for 15-20 minutes, and then the temperature is raised to 1300-1350°C in an argon atmosphere, and the temperature is kept for 2.5-3 hours, and then cooled to room temperature, washed with distilled water, and dried at 100-110°C for 12-14 hours. The mass ratio of silicon powder to flake graphite is 1:2-3; The preparation method of the modified 17-4PH high-toughness stainless steel material comprises the following steps: The titanium powder and graphene are added to anhydrous ethanol, ultrasonically mixed and then ball-milled, and then the temperature is raised to 550-600° C., and the temperature is kept at a pressure of 40-50 MPa for 4-6 minutes to prepare a premix; The premix is mixed evenly with stainless steel powder and aluminum powder, and kneaded at 100-160° C. for 20-30 minutes to obtain a mixed powder; The mixed powder is mixed with a binder, stirred at 160-165°C, and then granulated, injection molded, degreased, and heat treated; The specific method of the heat treatment is: solution treatment at 925-1040°C for 1-2h, and deep cooling treatment at (-10-0)°C for 1-2h.
2. The modified 17-4PH high-toughness stainless steel material according to claim 1, characterized in that: The added amount of titanium powder is 9% to 30% of the total mass of titanium powder and aluminum powder.
3. The modified 17-4PH high-toughness stainless steel material according to claim 1, characterized in that: The particle size of the silicon powder is 1-9 μm, and the particle size of the flake graphite is 45-75 μm.
4. The modified 17-4PH high-toughness stainless steel material according to claim 1, characterized in that: The particle size of the 17-4PH stainless steel powder is 15-53 μm.
5. The modified 17-4PH high-toughness stainless steel material according to claim 1, characterized in that: The tap density of the 304 stainless steel powder is 3.9-4.2 g / cm 3 , fluidity ≤30s / 50g, compressibility ≥6.55g / cm 3 .
Citation Information
Patent Citations
Preparation method for high strength and toughness modified high manganese steel based TiN steel bonded cemented carbide
CN106591711A
Stainless steel mixed material feedstock and preparing method thereof
CN109604584A
Composite powder with iron-based particles coated with graphene material
CN114423541A
Highly thermally conductive composite material
WO2006120803A1